Public Interest in Private Language Education Institutions: An Integrative Multidimensional Analysis - Ferry Ferdiansyah; Toufik Bouakel (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to analyze the multidimensional determinants of public interest in EF English First Pamulang Barat and to identify the most dominant factors influencing community enrollment decisions in a private language education institution. Methodology: This research employed a descriptive quantitative survey design. Data were collected using a structured Likert-scale questionnaire distributed to 36 respondents selected through simple random sampling. Data were analyzed using descriptive statistical percentage analysis with SPSS software to measure dimensional contributions to public interest. Main Findings: The overall public interest level reached 79.9% (Good category). All ten examined dimensions positively influenced public interest. Official certificates and diplomas obtained the highest score (85%), followed by small-class effectiveness (84%) and course consultant facilities (83.5%). Replacement classes received the lowest score (72%). Certification was identified as the most dominant determinant Novelty/Originality of this study: This study offers a multidimensional quantitative mapping of public interest by ranking ten institutional determinants within a private language education context. It highlights certification as the dominant predictor, providing new insight into credential-oriented decision-making behavior and advancing understanding of institutional credibility in educational choice.